Venture Capital and Strategic Development of Innovative Business - Yurynets, Zoryna; Yurynets, Rostyslav (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
One of the most important sources for improving the financial support of innovative activity is venture capital. The development of venture financing in developed countries is one of the defining areas of support for medium and small innovative businesses. The purpose of the article is to identify the key features of venture capital, the selection of structural characteristics of venture capital, and the functional features of venture financing for the strategic development of innovative businesses. The survey is based on the following methods: analysis, systematization, and generalization to identify the key features of venture capital, as well as to select structural characteristics of venture capital, and the functional features of venture financing; tabular representation for the visual display of the results of research and analytical data. The article analyzes the interpretations of venture capital. A significant expansion of the key features of venture capital was noted. The structural characteristics of venture capital for the strategic development of innovative businesses are highlighted, which are systematized according to the following signs: elements of the classic form of venture capital, functions of venture capital, characteristics of the venture capital market, phases of the venture capital investment process, reasons for the refusal to receive venture capital, results from the implementation of venture capital at the macroeconomic level. Functional features of venture financing for the strategic development of innovative businesses must be considered in the context of such features forms of venture financing, types of venture financing, features that are characteristic of venture financing, steps of the venture financing process, stages of venture financing, the most common exit strategy for venture capital investors, principles of venture financing, advantages of venture financing, disadvantages of venture financing. The obtained results are the basis for further scientific research in the part of venture financing of the strategic development of innovative businesses in Ukraine and attracting investments for the development of innovative activity.